DESIGNING HYPOTHETICAL LEARNING TRAJECTORIES FOR SET THEORY USING SCHOOL SNACK CONTEXTS IN MIDDLE SCHOOL - Muhtadi, Dedi; Sukirwan, Sukirwan; Yulianto, Eko; Fauzi, Rival Muhamad (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
This study aims to design and implement Hypothetical Learning Trajectory (HLT) on set material with the context of school snacks for Junior High School students. The main focus of this study is to support students' understanding of basic set concepts, such as subsets, intersections, and unions, through a contextual approach that is relevant to students' daily lives. The research method used is educational design research, which includes the planning, implementation, and analysis phases of learning outcomes. The subjects of the study were grade VII students at a junior high school in Tasikmalaya City. The research instruments included: observation sheets, concept understanding tests, and interviews to explore students' thinking processes during learning. The results showed that the use of the school snack context was relevant to the topic of sets and was able to increase students' interest and motivation in learning set material. Students' conceptual understanding also increased significantly, especially in identifying set elements, as well as understanding intersections and unions between sets through visual representations and group activities. The discussion of these results emphasizes that HLT with everyday contexts, such as school snacks, provides opportunities to link abstract material to students' real experiences, thus facilitating meaningful learning. The implementation of this research provides practical implications for teachers in designing context-based learning that can be used for other materials, as well as a reference for developing a curriculum that is more relevant to life.